«Non è nel mondo magior passïone». Appunti sulla gelosia nell’Inamoramento de Orlando - Decaria, Alessio (Griseldaonline, 2019)
The essay focuses on the representation of jealousy through the analysis of some episodes of Boiardo's Inamoramento de Orlando. For each of these parts of the poem the author tries to highlight the influence of the various classical and medieval models, also defining both the moral implications of this passion and its narrative functions within the poem.